2017
DOI: 10.1038/cddis.2017.311
|View full text |Cite|
|
Sign up to set email alerts
|

Linc-DYNC2H1-4 promotes EMT and CSC phenotypes by acting as a sponge of miR-145 in pancreatic cancer cells

Abstract: The acquisition of epithelial–mesenchymal transition (EMT) and/or existence of a sub-population of cancer stem-like cells (CSC) are associated with malignant behavior and chemoresistance. To identify which factor could promote EMT and CSC formation and uncover the mechanistic role of such factor is important for novel and targeted therapies. In the present study, we found that the long intergenic non-coding RNA linc-DYNC2H1-4 was upregulated in pancreatic cancer cell line BxPC-3-Gem with acquired gemcitabine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…Gemcitabine is the standard of care for PDAC, and several miRNAs have been described to be related to Gemcitabine response. miR-145, acting as sponge for the long intergenic ncRNAs (lincRNAs) linc-DYNC2H1-4, regulates EMT and CSC properties, impacting resistance to Gemcitabine in PDAC cells [130]. miR-205, a miRNA associated to CSC phenotypes in PDAC, is highly downregulated in Gemcitabine-resistant cells, and a reduction in CSCs, EMT and chemoresistance markers is observed when miR-205 is overexpressed, strongly suggesting that miR-205 re-sensitizes Gemcitabine-resistant PDAC cells to Gemcitabine [131].…”
Section: Role Of Mirnas In Cscsmentioning
confidence: 99%
“…Gemcitabine is the standard of care for PDAC, and several miRNAs have been described to be related to Gemcitabine response. miR-145, acting as sponge for the long intergenic ncRNAs (lincRNAs) linc-DYNC2H1-4, regulates EMT and CSC properties, impacting resistance to Gemcitabine in PDAC cells [130]. miR-205, a miRNA associated to CSC phenotypes in PDAC, is highly downregulated in Gemcitabine-resistant cells, and a reduction in CSCs, EMT and chemoresistance markers is observed when miR-205 is overexpressed, strongly suggesting that miR-205 re-sensitizes Gemcitabine-resistant PDAC cells to Gemcitabine [131].…”
Section: Role Of Mirnas In Cscsmentioning
confidence: 99%
“…The underlying mechanisms of PDAC have been linked to long non-coding RNAs (lncRNAs) 2 , 3 . The discovery of lncRNAs has been one of the most unexpected findings of the genomics era and provides a promising avenue for gaining biological insights 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have been reported as oncogenes or tumor suppressor genes, which regulate tumorigenesis and metastasis through targeting various genes that are abnormally expressed in cancer cells (11). As a tumor suppressive miRNA, miR-145 has been reported to be decreased in numerous types of human cancer, including pancreatic cancer (12), prostate cancer (13), cervical cancer (14), gastric cancer (15), oral cancer (16), colorectal cancer (17), breast cancer (18), bladder cancer (19) and melanoma (20). These previous studies have indicated that miR-145 may suppress the growth, migration and invasion of cancer cells, and inhibit tumorigenesis by targeting various genes that are abnormally expressed in tumors.…”
Section: Introductionmentioning
confidence: 99%